(untitled) (Bangladesh Journal of Pharmacology, 2013)
Statins are highly effective in managing hypercholesterolaemia in patients with or without chronic heart disease due to extensive evidence for safety, efficacy and cost effectiveness. Observational cross sectional retrospective cohort study was done in approximately 200 primary care practices in Scotland. Frequency, rates and time trends for statin prescriptions together with demographic data and the prescribing patterns for high dose simvastatin and newer statins in its place was measured. 63%, 27%, 5%, 4% and 1% patients were prescribed simvastatin, atorvastatin, pravastatin, rosuvastatin and fluvastatin respectively (n=1,91370). Prevalence for individual statin as well as for all statin prescriptions, significantly increased (p<0.05). Except rosuvastatin the incidence of other statins prescription significantly decreased (p<0.05). The highest number of patients, 884 (24%) switched to atorvastatin from high dose simvastatin. Increase in prevalent use and decrease in incident use of statins, implies the diminished cardiovascular disease related mortality and subsequent increased life expectancy of patients with cardiovascular disease.